Neural mechanisms of emotion during shifting perspectives and recognizing new information: An fMRI study. - Kazutaka Ueda; Xiaoxiang Wu; Hideyoshi Yanagisawa (PLoS ONE)
In generating novel ideas during the creative process, what ignites positive emotions like "Aha" experiences of insight? This study explored this by validating the biological plausibility of a mathematical model predicting emotions when shifting perspectives to recognize alternate information regarding an event. Using functional magnetic resonance imaging, we assessed brain activity as participants watched card magic videos with experimentally varied ease of information recognition. The results indicated that when shifting from certain to uncertain belief-based recognition, subjective interest arises if the new recognition is distant from the prior certain belief but close to the subsequent uncertain belief, accompanied by brain activations related to positive emotions. These findings suggest that interest emerges when deviating from conventional ideas towards unexpected yet easily comprehensible new ones, providing strategic insights for ideation.